FINANCIAL LITERACY IMPACT ON FINANCIAL BEHAVIOR AMONG STUDENTS IN BANDUNG - Rais Mubarak, Achmad
In Indonesia, especially in Bandung, one of the cities known for its educational environment, it can also be called an educational hub where the financial sector continues to increase, requiring the younger generation to understand financial concepts. news in 2022 from the Financial Services Authority (OJK) or the Indonesian Financial Services Authority that there is a gap between financial literacy and financial inclusion, where financial literacy is at 49.5 percent and financial inclusion is at 85 percent. From this OJK tries to encourage financial literacy of Indonesian citizens. It is known that for someone to have financial freedom, they need good financial management and financial decisions, but will the small percentage of Indonesian citizens' financial literacy mean that Indonesian citizens cannot gain financial freedom. This dissertation was created with the aim of finding out whether there is a relationship between a person's financial literacy and their financial behavior, which includes saving, spendings, investing, etc.